Psychological distress and unmet mental health needs among urban taxi drivers: A cross-sectional survey. (May 2018) - Davidson, Sandra; Wadley, Greg; Reavley, Nicola; Gunn, Jane; Fletcher, Susan
Objectives: The taxi industry relies on a male-dominated, predominately immigrant workforce who face multiple risk factors for poor mental health including shift work, low pay and threats of violence. Despite these risk factors, no previous study has documented the prevalence of psychological distress in the taxi industry. We investigated psychological distress among urban taxi drivers and explored the factors associated with high levels of distress. Method: A total of 380 taxi drivers were surveyed at the Melbourne Airport holding yard between September 2016 and March 2017. Psychological distress was measured using the K10. Logistic regression models were used to estimate the association between high levels of psychological distress and migration, work patterns, potentially traumatic events, health care use and social connectedness. Results: A third (33%) of drivers had very high (K10 ⩾ 30) levels of distress and 28% had high (K10 = 22–29) levels of distress. Trauma was significantly associated with high levels of psychological distress, and rates of trauma were much higher among drivers than among the Australian population. Despite high levels of distress, drivers were no more likely than other Australian men to visit a health professional. Conclusion: Urban taxi drivers are at very high risk for mental health problems, yet the mental health needs of this largely immigrant workforce has gone largely unnoticed. Interventions tailored to the unique characteristics of the job and the demographic composition of the workforce are urgently needed.